2002
DOI: 10.1542/peds.109.5.833
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Celiac Disease After Onset of Type 1 Diabetes: A 6-Year Prospective Longitudinal Study

Abstract: The prevalence of celiac disease in patients with type 1 diabetes is approximately 20 times higher than in the general population. Sixty percent of cases are already present at diabetes onset, mostly undetected, but an additional 40% of patients develop celiac disease a few years after diabetes onset. Extending screening programs for celiac disease after the onset of type 1 diabetes is recommended, even in the absence of clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
165
4
28

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(236 citation statements)
references
References 33 publications
39
165
4
28
Order By: Relevance
“…In a prospective 6-year study on children who had diabetes and CD, no patients were found to develop CD Ͼ4 years after diabetes onset. 23 Therefore, we suggest that screening for CD should be performed annually on patients with negative CD serology at diabetes onset for a minimal duration of 4 years. This strategy should be evaluated in prospective studies to confirm that antitTG limited testing is a cost-effective method to identify CD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a prospective 6-year study on children who had diabetes and CD, no patients were found to develop CD Ͼ4 years after diabetes onset. 23 Therefore, we suggest that screening for CD should be performed annually on patients with negative CD serology at diabetes onset for a minimal duration of 4 years. This strategy should be evaluated in prospective studies to confirm that antitTG limited testing is a cost-effective method to identify CD.…”
Section: Resultsmentioning
confidence: 99%
“…More often, CD is diagnosed shortly after or sometimes years after the onset of type 1 diabetes. 5,[21][22][23] To determine the temporal relationship between the onset of type 1 diabetes and CD, we tested for anti-tTG in the initial serum taken at the onset of diabetes using our serum library. The retroactive screening showed that only 1 of 11 patients (patient 11)-the one with a positive jejunal biopsy-was anti-tTG negative at the onset of the type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…2 It is also unclear why patients with recently developed T1D have a higher likelihood of developing CD than patients with long-lasting T1D. 36,45 It is possible that a subgroup of T1D patients might have certain specific characteristics that condition the development T1D and CD in the same person.…”
Section: Discussionmentioning
confidence: 99%
“…In Italy, the prevalence of celiac disease in children with type 1 diabetes is around 7% [9,10] , 3.6% of which at type 1 diabetes onset [9] , at a younger age [10] and in boys [10] ; moreover, according to a study by Salardi et al [11] , the prevalence of celiac disease has significantly increased since 1994 (10.6% vs 6.6%, P = 0.015), probably due to changes in environmental factors, namely, eating habits and viral infections.…”
Section: Introductionmentioning
confidence: 99%